2012
DOI: 10.5130/ajceb.v9i2.3020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Levels of Project Planning and their Effects on Performance in the Nigerian Construction Industry

Abstract: This study compares the level of project planning on public and private sectors projects and its impact on performance. The purpose is to create awareness of the level and effectiveness of the planning done by public and private clients in the delivery of construction projects. A questionnaire survey administered to a sample of 130 client representatives selected by stratifi ed random sampling from the population of public and private clients in the Nigerian construction industry is used and analysed using des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…The preliminary survey was conducted because there is no reliable comprehensive data of clients in the study population. This is consistent with studies such as Idoro (2012). The questionnaires were distributed to owners/clients and/or their representatives.…”
Section: Sampling and Data Collectionsupporting
confidence: 70%
“…The preliminary survey was conducted because there is no reliable comprehensive data of clients in the study population. This is consistent with studies such as Idoro (2012). The questionnaires were distributed to owners/clients and/or their representatives.…”
Section: Sampling and Data Collectionsupporting
confidence: 70%
“…Dlakwa and Culpin (1990) and Adekoya (2003) identified government fiscal policies as one of the factors affecting the cost of building materials in the Nigerian construction industry. However, findings of other researchers, Jagboro and Owoeye (2004); Mojekwu, Idowu, and Sode (2013); and Idoro and Jolaiya (2010), concluded that factors such as the change in government policies and legislations, scarcity of building raw materials, fluctuation in the cost of fuel and power supply, inadequate infrastructural facilities, corruption, fluctuation in the cost of plant and labor, seasonal changes, fluctuation in the cost of transportation and distribution, political interference, local taxes and charges, fluctuation on cost of raw materials, fluctuation in the interest rates and the cost of finance, the inflation, and fluctuation in the exchange rate of Naira were many of the recipes for the rising cost of building materials in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Ibn-Homaid (2002) and the report of UNCHS (1993) found that building materials remain the most significant input in project development and play a very important role in the delivery of construction projects. Buttressing this view, Jagboro and Owoeye (2004) and Idoro and Jolaiya (2010) find that building materials alone account for 50% to 60% of project cost and control about 80% of its schedule.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Project success and performance to a greater extent depend on planning; therefore, it plays a pivotal role during the phases of project formation (Naeem et al, 2018). Idoro (2012) argues that planning is a thorough continuous process for delivering a project. Many empirical studies regarding success factors of project management indicated planning as the key contributor towards project success (Aronson & Lechlier, 2009;Murphy et al, 1974;Slevin & Pinto, 1987).…”
Section: Introductionmentioning
confidence: 99%